2013
DOI: 10.1007/s11414-013-9376-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Outpatient Mental Health Service Use of Transition-Age Youth in the USA

Abstract: This study examines diagnostic and service utilization patterns of transition-age youth in outpatient care derived from the 2007 nationally representative Client/Patient Sample Survey. Comparisons between 16-17, 18-21, and 22-25 year olds are highlighted. Among transition-age outpatients, the oldest youth had the highest rates of depression and bipolar disorder and co-occurring medical and substance use problems. Controlling for sociodemographic and clinical characteristics, 18-21 year olds were less likely to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 32 publications
3
18
0
Order By: Relevance
“…The decline in service use may differ based upon service type. When controlling for young adult clinical profiles and demographic characteristics, Pottick et al found a marked decline in receipt of individual office-based therapy for 18–21 year olds when compared to 16–17 year olds (3). However, no differences were found between these age groups in receipt of psychotropic medications (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The decline in service use may differ based upon service type. When controlling for young adult clinical profiles and demographic characteristics, Pottick et al found a marked decline in receipt of individual office-based therapy for 18–21 year olds when compared to 16–17 year olds (3). However, no differences were found between these age groups in receipt of psychotropic medications (3).…”
mentioning
confidence: 99%
“…When controlling for young adult clinical profiles and demographic characteristics, Pottick et al found a marked decline in receipt of individual office-based therapy for 18–21 year olds when compared to 16–17 year olds (3). However, no differences were found between these age groups in receipt of psychotropic medications (3). Observed decreases in service use coincide with an increase in the prevalence of mental disorders among adolescents aged 13–18 (4).…”
mentioning
confidence: 99%
“…We also examined the effects of race/ethnicity and age on psychiatric treatment dropout, which have been shown to affect treatment engagement (26, 27, 28) but have not been examined among pregnant women. Our study found a high rate of treatment discontinuation during pregnancy while highlighting the benefit of engaging reproductive aged women in psychotherapy pre-conception.…”
Section: Discussionmentioning
confidence: 99%
“…These and other findings can help understand organizational practices and policies which enable transitions and thus provide gateways to young adults who have mental health problems. 27, 61 …”
Section: Implications For Behavioral Healthmentioning
confidence: 99%